Eksperimen Pembelajaran Matematika Dengan Model Pembelajaran Student Team Achievement Division (STAD) Dan Snowball Throwing Terhadap Hasil Belajar Matematika Ditinjau Dari Minat Belajar Siswa - Tama, Michael Dhani Putra, Muhammad Noor Kholid, S.Pd., M.Pd (2016)
This study aims to determine the effect of differences in learning model Student Team Achievement (STAD), Snowball Throwing (ST), and Expository and differences of influence student interest towards mathematics learning outcomes. The population used to study the entire seventhh grade students of SMPN 1 Cepogo in the academic year 2016/2017. Sample was taken by cluster random sampling method was obtained grade E, C and A. The data used include: 1) The score of daily tests CHAPTER I taken by method of documentation, 2) Interest in learning mathematics taken by questionnaire, and 3) Scores of mathematics learning outcomes obtained by test. A test instrument was using validity and reliability. Balance test is using one way analysis of variance with different cells and also test the hypothesis by using two-way analysis of variance with different cells. Previous normality test was using methods Liliefors and homogeneity of variance using Bartlett method. The whole test was using a significance level of 5%. Hypothesis test results conclude that: 1) Model STAD gives a better effect than learning model of ST and expository and learning model of ST as good as expository learning models, 2) Students with an interest in learning high had equally good results with students with interest in learning currently, students with a high interest in learning had better results than students with low learning interest , and students with an interest in learning were having equally good results with students with low learning interest, and 3) there was no interaction between the learning model and interest in learning to mathematics learning outcomes.